Computer simulations to optimize the design of marker-assisted backcrossing for high-throughput marker systems - Herzog, Eva; Justus Liebig University Giessen (My University, 2014)
Marker-assisted backcrossing (MABC) is to date the most successful application of DNA markers in plant breeding. Nevertheless, the large-scale implementation of genome-wide background selection with DNA markers has lagged behind expectations due to the high costs of marker analysis. It has been hypothesized that this problem will be overcome by high-throughput (HT) marker assays which enable genotyping a high number of marker loci at comparatively low cost per individual marker data point. The optimum backcross designs for HT assays have previously not been investigated.The objective of the study was therefore the development of novel selection strategies for the efficient use of HT assays in different applications of MABC. For this purpose, computer simulations were employed.The cost-efficiency of HT assays compared to SM assays was greatest in short, highly intense backcross programs, while it decreased with increasing marker fixation in advanced backcross generations.The optimum breeding designs for SM assays were characterized by increasing marker densities and population sizes. The optimum breeding designs for HT assays were in contrast characterized by few backcross generations, constant marker densities and constant or decreasing population sizes.Combining SM and HT assays at different stages of a backcross program reduced the cost of marker analysis compared to using only HT assays.Using HT assays with a combined selection index for foreground and background selection reduces the logistic efforts and allows more differentiated selection decisions.It can be concluded that HT assays have the potential to increase the relative efficiency of background selection for many applications of MABC.

Markergestützte Rückkreuzung ist bislang die erfolgreichste Anwendung von DNA-Markern in der Pflanzenzüchtung. Dennoch ist die Anwendung der genomweiten Hintergrundselektion zur Wiederherstellung des Rezipientengenoms hinter den Erwartungen zurückgeblieben. Die Ursachen lagen in den hohen Kosten für die Vielzahl der benötigten Einzelmarkeranalysen begründet. Eine Lösung stellen Hochdurchsatzanalysen wie SNP-Chips dar, mit denen eine hohe Zahl von Markern zu vergleichsweise geringen Kosten pro Markerdatenpunkt genotypisiert werden kann. Die optimalen Selektionsstrategien für Hochdurchsatzmarkeranalysen wurden bislang noch nicht untersucht.Das Ziel der vorliegenden Arbeit war es daher, neue Strategien für den effizienten Einsatz von Hochdurchsatzmarkeranalysen in verschiedenen Anwendungen der markergestützten Rückkreuzung zu entwickeln. Zu diesem Zweck wurden Computersimulationen in verschiedenen Kulturarten durchgeführt.Die Kosteneffizienz der Hochdurchsatzsysteme war am größten in kurzen Rückkreuzungsprogrammen mit dem Ziel hohen Selektionsgewinns, nahm jedoch mit zunehmender Markerfixierung in fortgeschrittenen Rückkreuzungsgenerationen ab.Effiziente Zuchtschemata für Einzelmarkeranalysen waren durch ansteigende Markerdichten und Populationsgrößen gekennzeichnet. Im Gegensatz dazu waren optimale Zuchtschemata für Hochdurchsatzmarkeranalysen durch wenige Rückkreuzungsgenerationen, konstante Markerdichten und konstante oder abnehmende Populationsgrößen gekennzeichnet.Die Kombination von Einzelmarker- und Hochdurchsatzanalysen in verschiedenen Phasen eines Rückkreuzungsprogramms reduzierte die Kosten im Vergleich zur ausschließlichen Anwendung von Hochdurchsatzanalysen.Die Verwendung eines kombinierten Selektionsindexes für gleichzeitige Vorder- und Hintergrundselektion reduzierte en logistischen Aufwand und erlaubte differenzierte Selektionssentscheidungen.Hochdurchsatzmarkeranalysen können die Effizienz vieler Anwendungen der markergestützten Rückkreuzung im Vergleich zu Einzelmarkeranalysen erhöhen.
Computersimulationen zur Optimierung der markergestützten Rückkreuzung mit Hochdurchsatzmarkersystemen
Keywords: Agrarwissenschaften; Pflanzenzüchtung; Populationsgenetik; markergestützte Rückkreuzung; Computersimulation; Agricultural sciences; plant breeding; population genetics; marker-assisted backcrossing; computer simulation; ddc:630